Bridging the Knowledge Gap: Towards Establishing the Impact of Leadership Styles on Libyan Small Medium Enterprise Performance - Hamza Abdullfatah Momen , Dr. Siti Aida Samikon (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
SMEs throughout the globe are severely impacted by several challenges that impede the performance of entrepreneurs. Thus, the purpose of this paper is to identify the impact of leadership style on Libyans’ Small and Medium Enterprises (SMEs) performance. Required data was collected through a random method and a questionnaire administered on 258 managers of Libyan SMEs. This research suggested that Leaders must invest in training and development in order to advance their skills and abilities to carry out transformational and transactional leadership styles in their businesses.